Research on Development and Key Technologies of Intelligent Bed-jig System for Ship Sectional Construction. Issue 1 (April 2020) - Shen, Yubo; Wang, Rui; Liu, Mingzhi; Wang, Yueting; Chen, Mingshan; Zhao, Yaorong; Zhou, Honggen
Abstract: Nowadays, the existing bed-jig is difficult to meet the requirements of modern ship intelligent manufacturing. This is mainly due to the following three problems: one is the redundancy of location arrangement, the other is the difficulty of moving, and the third is the discontinuity of height adjustment. For the segmental construction of ships, this paper puts forward the research and development of intelligent bed-jig system. Breakthroughs have been made in key technologies, including dynamic placement of jig and dynamic adjustment of support height. It also realizes the intelligent decision-making of process data in ship sectional construction. In general, it provides a technical basis for intelligent manufacturing of ship segments.